Amplification of femtosecond and picosecond pulses using large mode area Erbium-doped fiber at 1530 nm wavelength. (January 2022) - Rehan, Mohd; Kumar, Aashish; Rastogi, Vipul
Highlights: Presented a LMA-EDF to amplify the short duration high peak power pulses. Pumped at 980 nm with 10 W pump power and achieved the gain 17 dB/m. LMA increases the power handling capacity and damage threshold of the fiber. Achieved pulses of 20 fs with 2.6 MW peak power. Achieved pulses of 65 ps with 26 MW peak power. Abstract: We present amplification of short and ultrashort laser pulses at 1530-nm center wavelength using a large mode area Er-doped fiber (LMA-EDF). The mode area of about 1700 μm 2 tremendously increases the power handling capacity of the fiber and helps in achieving up to ∼ 17 dB/m gain with 10 W power of 980-nm wavelength pump. The LMA fiber used here is a 3-layer W-type fiber designed to have effective single mode operation with higher order mode discrimination and sufficient mode spacing between the first few modes to avoid any possible mode coupling. In particular, we numerically demonstrate the amplification of 300 fs, 1 kW peak power pulses to ∼ 20 fs, ∼2.6 MW peak power pulses in 1.5-m propagation distance, and of 50 ps, 1 kW peak power pulses to ∼ 65 ps, ∼26 MW peak power pulses in 3-m propagation distance of the LMA-EDF. The generated pulses would be useful in applications such as eye-safe remote sensing and 3D laser processing of silicon.